Investigating genomic instability features in hereditary cancers - Chu, Yuen Theng (Nanyang Technological University, 2020)
Cancer refers to group of diseases characterised by uncontrolled proliferation. Various pathways safeguard a cell from cancer and a single cell usually requires multiple mutations to become cancerous. Mutation resulting in genome instability predisposes an individual to accumulate mutations, ultimately leading to cancer. DNA damage causing double stranded breaks (DSBs) are efficiently repaired via non homologous end joining (NHEJ) or Homologous recombination (HR). Our focus is on mechanisms of damage response proteins, RAD51C and BRCA1 in HR, an error free repair that involves resolution of holiday junctions at sites of homologous recombination exchange of DNA. Defects in HR affects sensitivity of cancer cells to chemotherapeutic drugs, thus a proper understanding of DDR proteins involved in HR is required. Here we review the role of RAD51C on preserving genome stability through observing characteristics of variants upon drug treatments. We found that a specific variant A87E accumulated less breaks compared to other variants E49K and L134S upon ATRi and MMC treatment. BrdU incorporation was proportionally increased relative to damage observed, suggesting the role of DSBs in inducing repair. S33pRPA expression was also decreased upon etoposide treatment in BRCA1 deficient cells. Together, these results demonstrate that certain mutations exhibit increased resistance to specific drugs.